RAD-Seq and Ecological Niche Reveal Genetic Diversity, Phylogeny, and Geographic Distribution of Kadsura interior and Its Closely Related Species - Dong, Yuqing; Wei, Xueping; Qiang, Tingyan; Liu, Jiushi; Che, Peng; Qi, Yaodong; Zhang, Bengang; Liu, Haitao (Frontiers in Plant Science, 2022)
Most plants of Kadsura have economic value and medicinal application. Among them, K. interior and its closely related species have been demonstrated to have definite efficacy. However, the taxonomy and phylogenetic relationship of Kadsura in terms of morphology and commonly used gene regions remained controversial, which adversely affects its rational application. In this study, a total of 107 individuals of K. interior, K. heteroclita, K. longipedunculata, K. oblongifolia, and K. coccinea were studied from the perspectives of genetic diversity, phylogeny, and ecology via single nucleotide polymorphisms (SNPs) developed through restriction site-associated DNA sequencing (RAD-seq). Based on these SNPs, genetic diversity, phylogenetic reconstruction, and population genetic structure were first analyzed. Subsequently, divergence time estimation and differentiation scenario simulation were performed. Meanwhile, according to species distribution records and bioclimatic variables, the Last Glacial Maximum and modern potential distributions of five species were constructed, and main ecological factors affecting the distribution of different species were extracted. The FST calculated showed that there was a moderate degree of differentiation among K. heteroclita, K. longipedunculata, and K. oblongifolia, and there was a high degree of genetic differentiation between K. interior and the above species. Phylogenetic tree indicated that each of the species was monophyletic in the phylogenetic tree. The results of population genetic structure and divergence scenario simulation and D-Statistics showed that there were admixture and gene flow among K. heteroclita, K. longipedunculata, and K. oblongifolia. The results of ecological niche modeling indicated that the distribution areas and the bioclimatic variables affecting the distribution of K. interior and its related species were very different. This study explored the differences in genetic divergence and geographical distribution patterns of K. interior and its related species, clarifying the uniqueness of K. interior compared with its relatives and providing a reference for their rational application in the future.